Parameter Determination Method of Cassie-Mayr Hybrid Arc Model Based on Magnetohydrodynamics Plasma Theory - Yang, Fan; Tang, Zhaohui; Shen, Yu; Su, Lei; Yang, Zhichun (Frontiers in Energy Research, 2022)
This paper proposes an improved alternating current (AC) arc model based on Cassie-Mayr hybrid model and magnetohydrodynamics (MHD) theory. The undetermined parameters of traditional Cassie-Mayr arc model are mainly obtained by subjective methods such as empirical value, approximate expression and indirect estimation which are complex, inaccurate and dependent on experimental data. To overcome these disadvantages, an axisymmetric two-dimensional arc model is established based on the MHD theory, and the undetermined parameter values of Cassie-Mayr hybrid arc model are obtained based on the results of MHD numerical simulation. The accuracy of the proposed modification Cassie-Mayr model is verified by comparing with experimental data and the results of the modification Cassie-Mayr model, traditional Mayr model and Cassie model is discussed. The arc characteristics of serval loads is studied and analyzed based on the modification model.